Psychologists and race : exploring the identities of South African trainee clinical psychologists with reference to working in multiracial contexts - Nair, Sorayah (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhil (Psychology))—University of Stellenbosch, 2008.